2016
DOI: 10.1556/168.2016.17.1.13
|View full text |Cite
|
Sign up to set email alerts
|

How do diversity and functional nestedness of bird communities respond to changes in the landscape caused by eucalyptus plantations?

Abstract: Abstract:Studies of functional diversity can help to understand processes that determine the presence of species in different habitats. Measurement of functional diversity in silviculture areas is important because different functional traits can show different responses to this landscape alteration, and therefore ecological functions can be affected. This study evaluated functional and taxonomic differences in bird assemblages in a native forest and eucalyptus plantations, and also assessed the functional nes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…To the best of our knowledge, our study is the first to investigate the taxonomic, functional and phylogenetic nestedness simultaneously. So far, previous studies often focused on taxonomic nestedness of fauna assemblages (e.g., Cook & Quinn, 1995; Matthews, Cottee‐Jones, et al, 2015; Wright et al, 1998), while only a few studies begin to examine functional or phylogenetic nestedness (Almeida‐Gomes et al, 2019; Jacoboski et al, 2016; Matthews, Sheard, et al, 2015). In our study, the functional and phylogenetic nestedness analyses showed that isolation was an additional nestedness driver, whereas this process was overlooked when only considered taxonomic nestedness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, our study is the first to investigate the taxonomic, functional and phylogenetic nestedness simultaneously. So far, previous studies often focused on taxonomic nestedness of fauna assemblages (e.g., Cook & Quinn, 1995; Matthews, Cottee‐Jones, et al, 2015; Wright et al, 1998), while only a few studies begin to examine functional or phylogenetic nestedness (Almeida‐Gomes et al, 2019; Jacoboski et al, 2016; Matthews, Sheard, et al, 2015). In our study, the functional and phylogenetic nestedness analyses showed that isolation was an additional nestedness driver, whereas this process was overlooked when only considered taxonomic nestedness.…”
Section: Discussionmentioning
confidence: 99%
“…As illustrated by Melo et al (2014) and similar studies (e.g. Almeida‐Gomes et al, 2019; Jacoboski et al, 2016), nestedness from multiple facets of biodiversity can help reveal the linkages between species' requirements and their environment, which could offer more information on mechanisms underlying community assembly than those focused purely on species taxonomic composition.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although tree plantations may maintain some of the characteristics of natural forests, such as tall and high canopy cover, and deep litter layer, they are typically unsuitable for many edge-intolerant species and forest specialists (Filloy et al 2010;Dias et al 2013), leading to a decline in the taxonomic, functional and phylogenetic diversity of the local assemblages (Machado et al 2012;Gangenova et al 2018;Jacoboski et al 2019). Such declines caused by the local extinction of intolerant and specialist species triggered by the establishment of tree plantations have been observed for mammals (Barlow et al 2007a;Yue et al 2015), birds (Dias et al 2013;Corbelli et al 2015;Jacoboski et al 2016Jacoboski et al , 2019, reptiles (Saccol et al 2017) and anurans (Saccol et al 2017;Gangenova et al 2018). In the specific case of the anurans, the effects of tree plantations on leaf-litter frog assemblages are still poorly understood (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already underlined the negative effects on native species and their related ecosystem functions due to the expansion of forest plantations (Tererai et al, 2013). Besides, the majority of studies on biodiversity changes among different plantation ages have been conducted mainly in forest biomes (Barlow et al, 2007;Jacoboski et al, 2016;Proença et al, 2010;Wu et al, 2015), showing that mature plantations contribute to maintain biodiversity better than young plantations. The opposite pattern was observed for bird and ant communities in tree plantations developed in grassland sites, where the richness and abundance were the lowest in mature plantations and highest in the grasslands (Corbelli et al, 2015;Filloy et al, 2010;Phifer et al, 2016;Santoandré et al, 2019).…”
Section: Introductionmentioning
confidence: 99%